2004
DOI: 10.1111/j.1398-9995.2004.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunotherapy abrogates seasonal bronchial hyperresponsiveness in children with Parietaria‐induced respiratory allergy: a randomized controlled trial†

Abstract: Our data show that SLIT abrogates the seasonal bronchial hyperreactivity in children with asthma due to Parietaria. This may be regarded as an indirect evidence of the effect on bronchial inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…This might suggest that SLIT acts also on bronchial allergic inflammation, although it is well known that bronchial hyperreactivity is only in part attributable to inflammation itself. 22 The effect is consistent with that described in previous clinical trials with SLIT 23,24 and the injection route. 25 Concerning the effect on local allergic inflammation, this study offered the opportunity to follow up the effects on nasal eosinophils under the natural exposure to pollen and confirmed that the effect was consistent with the time.…”
Section: Discussionsupporting
confidence: 90%
“…This might suggest that SLIT acts also on bronchial allergic inflammation, although it is well known that bronchial hyperreactivity is only in part attributable to inflammation itself. 22 The effect is consistent with that described in previous clinical trials with SLIT 23,24 and the injection route. 25 Concerning the effect on local allergic inflammation, this study offered the opportunity to follow up the effects on nasal eosinophils under the natural exposure to pollen and confirmed that the effect was consistent with the time.…”
Section: Discussionsupporting
confidence: 90%
“…39,75,81 In studies that included 80% of all patients who underwent nonspecific bronchial challenge, there was a statistically significant increase in mean threshold that occurred in all studies with more than 12 months of SLIT administration. 31,35,39,41,57,92 In one study with serial measures of methacholine sensitivity, there was a progressive increase in threshold from 6 months to 18 to 24 months of SLIT. 35 In studies that included 71% of all patients who underwent specific nasal challenge, there was a statistically significant increase in mean threshold.…”
Section: Provocation Testsmentioning
confidence: 95%
“…A combined grass/olive extract vs. placebo administered to children 6 months before the pollen season did not result in different asthma outcomes between the groups, probably due to the low allergen season in which the study was conducted [161]. For Parietaria and tree polleninduced asthma, SLIT has shown to be effective in reduction of pulmonary symptoms [162,163], to the same extend as inhaled fluticasone propionate [164].…”
Section: Pediatric Populationsmentioning
confidence: 99%